PERLINDUNGAN HUKUM TERHADAP FISIOTERAPIS DALAM PELAYAAN FISIOTERAPI MANDIRI DI KOTA DENPASAR - Anak Agung Sagung Ngurah, Indradewi; Muhammad Zulkarnain , Rosyid (Fakultas Hukum Universitas Dwijendra, 2026)
One of the rights that must be realized in providing various health efforts to the entire community is the implementation of quality health development. One form of health efforts is physiotherapy services. When practicing physiotherapists provide assessment sheets to patients and written and oral explanations regarding the duration and type of therapy to be given. Some cases that appear in the public provide a warning that health workers in carrying out their duties must be careful and responsible, and legal protection is needed to prevent errors of omission, which result in lawsuits. The purpose of this study is how the implementation of legal protection and what obstacles exist in the implementation of legal protection to physiotherapists as independent physiotherapy in Denpasar City. The research uses empirical research method and descriptive approach. Data were obtained from interviews with representatives of the Denpasar Branch Physiotherapy Association and independent Physiotherapy Practices in Denpasar City. The results of this study show that the physiotherapy profession often faces interventions from other professions, especially through referral letters or written requests that mention specific physiotherapy technology interventions. In the implementation of home visits, physiotherapists explain repeatedly about the importance of Informed consent, because during the action during home visits it will greatly complicate the action and reduce concentration during therapy due to limited time, infrastructure and conditions are not conducive. Conclusion of this study Legal protection for physiotherapists is crucial to ensure safe, ethical and professional practice. Clear regulations help regulate the rights and obligations of health workers and protect patients from potential violations. It is recommended that health workers need to keep abreast of regulatory developments to remain relevant and comply with established standards.